2022
DOI: 10.2174/1573402117666210921121622
|View full text |Cite
|
Sign up to set email alerts
|

The High Potency of Polymeric Nanoparticles in the Drug Delivery System for Hypertension Treatment: A Systematic Review

Abstract: Background: Polymeric nanomaterials with size ranging from 10 to 1000 nm are one of the most widely used types of nanoparticles with ideal properties in the drug delivery systems. Here, we decided to systematically review the antihypertensive effects of polymeric nanomaterials in vitro, in vivo, and clinical trials. Methods: The present review was conducted based on the 06- PRISMA guideline; whereas five English databases, including Scopus, PubMed, Web of Science, EMBASE, and Google Scholar without time limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…We selected studies via PubMed search and evaluated references identified in key reviews. 2,3,6,[13][14][15] To limit the scope to those with the greatest translational potential, we included only articles published within the last 10 years. Furthermore, we included only studies assessing nanoformulations in vivo, including 1 patient study (Table S2).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected studies via PubMed search and evaluated references identified in key reviews. 2,3,6,[13][14][15] To limit the scope to those with the greatest translational potential, we included only articles published within the last 10 years. Furthermore, we included only studies assessing nanoformulations in vivo, including 1 patient study (Table S2).…”
Section: Reviewmentioning
confidence: 99%
“…1 Early hypertension stages lack specific clinical symptoms, but when left unchecked sufferers are at higher risk of heart failure, coronary artery disease, angina, myocardial infarction, thrombosis, and cerebral hemorrhage, which put the heart, brain, and kidneys at significant risk. 1,2 These numbers are severely exacerbated by poor patient compliance with medications due to frequent dosing requirements and undesirable side effects. Adding further complication is the prevalence of treatment-resistant hypertension, defined by BP remaining elevated despite treatment with 3 different classes of antihypertensives at optimal or maximal dosing concurrently.…”
mentioning
confidence: 99%
“…It is an essential technology used to selectively deliver a drug according to the site of the disease or to release the drug periodically while controlling the released amount. However, the effectiveness of these systems is still not satisfactory for clinical applications [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Several studies have been conducted to create micro- or nanosized ultrafine structures, based on micro- and nanotechnologies, to deliver cancer-killing drugs to cancer cells [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%